Attachment ability of combined biomimetic adhesive micro-textures of different shapes - David Badler; Yuri Kligerman; Haytam Kasem (Friction)
Abstract There are various potential applications of biomimetic adhesive solutions including climbing robotic systems, mobile sensor platforms, and biomedical applications such as patches for external use. Achieving resistance to both normal and tangential loads, however, is a critical issue that still needs to be addressed. Some animals have developed exceptional attachment mechanisms based on combined fibrillar elements of different shapes and functions. Experimental investigation of combined biomimetic adhesive micro-textures on tribological performances such as adhesion, friction, and peeling resistance is needed to apply this idea to the design of an artificial texture having similar “biomimetic” properties. In the present study, we demonstrate that combinations of different shapes of biomimetic adhesive micro-textures show increased efficiency under different contact environments and enable long-term adhesive solutions. Our work sheds light on combinations of different element shapes inspired by nature and their adhesive efficiency as a function of the ratio of each biomimetic element, as well as their spatial repartition.